2020
DOI: 10.1145/3401026
|View full text |Cite
|
Sign up to set email alerts
|

Generating Question Titles for Stack Overflow from Mined Code Snippets

Abstract: Stack Overflow has been heavily used by software developers as a popular way to seek programming-related information from peers via the internet. The Stack Overflow community recommends users to provide the related code snippet when they are creating a question to help others better understand it and offer their help. Previous studies have shown that a significant number of these questions are of low-quality and not attractive to other potential experts in Stack Overflow. These poorly asked questions are less … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…Until now, millions of developers use Stack Overflow to search for high-quality answers for their programming problems. Moreover, Stack Overflow becomes a knowledge base for developers to learn programming skills by browsing high-quality posts [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until now, millions of developers use Stack Overflow to search for high-quality answers for their programming problems. Moreover, Stack Overflow becomes a knowledge base for developers to learn programming skills by browsing high-quality posts [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…These low-quality question posts not only fail to get effective help, but also hinder the process of knowledge generation [6] [7]. To solve this problem, previous studies have been conducted on the quality prediction of the question posts [1], [8]- [13]. For example, Correa and Sureka [10] surveyed the closed problems in Stack Overflow and found that high-quality problems should contain enough code for others to reproduce the problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…• We collected more than 1M ⟨code snippet, question⟩ pairs from Stack Overflow, which covers a variety of programming languages (e.g., Python, Java, Javascript, C# and SQL). We have released our code 6 and datasets [17] to facilitate other researchers to repeat our work and verify their ideas. We also implemented a web service tool, named Code2Que to facilitate developers and inspire the follow-up work.…”
Section: Introductionmentioning
confidence: 99%